Evaluación de la agroindustria del almidon agrio de yuca (Manihot esculenta Crantz) en Córdoba y Sucre. - Villarraga, Erika C.; Lujan, Deivis E.; Salcedo, Jairo G.; Cadena, Marly P. (Universidad de Córdoba - UNICORDOBA, 2018)
Sumario (Es)